The Effectiveness of Pregnancy Training Class towards the Childbirth Preparation in Kendal Regency - Widiar, Restu; Soesanto, Soesanto; Deliana, Sri Maryati (Public Health Perspective Journal, 2018)
The mortality number of women (AKI) is one of the indicators which shows the maternal health degree. In Kendal Regency, this class has been socialized and conducted since the late 2009, but the decrease of AKI has not been significant yet. This study was aimed at analyzing the effectiveness of a childbirth preparation training in pregnant women class. By such objective, this study belongs to quasi-experiment with non-randomized control group pretest-posttest design. This design used purposive sampling and involved 60 pregnant women in trimester III who were divided into three groups as the sample, namely: two as experimental groups, and one as control group. Their data were analyzed by using one way ANOVA and Tamhane’s Post Hoc test. The results showed that there was a significant difference in the improvement of childbirth preparation of pregnant women viewed from the post-test and pre-test of the experimental group of A, B and control group showed by the result of one way ANOVA test with the p value of (0.000) < 0.05. According to the above findings, this study concludes that the giving of pregnancy training class with the slide media is more effective than the flipchart media in improving the childbirth preparation of pregnant women. It was showed by the result of Tamhane’s Post Hoc test, namely 0.000< 0.05 and N-gain value of 0.70 > 0.71.